Unfinished business. Bruce Kercher, An unruly child: a history of law in Australia - A. Frazer (Law Text Culture, 1997)
Until quite recently legal history, as practised and taught in Australian law schools has remained fixated on a narrow range of 'lawyers' law'. Legal history sought the legitimating foundations of the current legal system and profession, concentrating on constitutional issues dealing with the establishment of the higher courts and legislatures, or on the reception of English legal doctrines in Australia. The focus and assumptions of such accounts were decidedly Whiggish. The story of law in Australia was one of progress and reason, as manifested in the transplantation of British institutions and English common law. The professionalisation and modernisation of law which accompanied the wholesale importation of English reforms, were assumed to lead more or less inevitably to our current system of justice. This perspective has been challenged in recent years by scholars influenced by social history and cultural studies, and more interested in tracing the distinctiveness of Australian law as well as its social impact. Significantly, most of the reassessment has come from outside the law schools, from historians interested in law not as an object in itself, but as one of many sites of cultural conflict and social change.